Air Asia Crisis Communications Strategies and Malaysia Airlines: A Content Analysis - Ni Ketut Dimar Warsihantari; I Gusti Ngurah Putra (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2018)
The aviation industry is one of the most vulnerable industrial sectors to the crisis. Failure to manage the crisis they face can threaten their lives. Therefore, managers of airline companies are required to have the ability to manage crisis and communicate in crisis situations. Crisis communication strategy becomes an important part in crisis management. This study uses content analysis of the crisis communication strategies used by AirAsia and Malaysia Airlines in their respective aircraft accidents on December 28, 2014 and March 8, 2014. This research found that both companies were fast enough to respond to crises despite differences in strategy they use in responding the  crisis. AirAsia emphasizes the use of apology without ignoring compensating, while Malaysia Airlines emphasizes compensation without ignoring apology.